Kesanggupan pengunjung membayar untuk aktiviti dan menyumbang kepada tabung pemuliharaan di Taman Negara Endau-Rompin - Harun, Mohd. Azamrul (2007)
Study of willingness to pay on natural resources used is a field of study that explains about human perception and assessment to the resources. This study was conducted to find out the visitor willingness to pay (WTP) for activities and natural conservation at Endau-Rompin National Park. Contingent Valuation Method (CVM) is used in conducting this study. Results indicate that, visitor are willing to pay some of the charges. The study shows that the willingness to pay for entrance fee is RM5.58 and willingness to contribute to the conservation fund is RM3.22. The study indicates that visitor assume that government is responsible to conserve nature. The study also shows that there is no significant relationship between age, gender or occupation and the visitor’s willingness to pay.